Removable partial denture with telescopic overdenture - Riskani Djafri; Acing Habibie Mude (Indonesia Prosthodontic Association, 2023)
Telescopic dentures have better retention and stability than conventional complete dentures. It improves mastica-tory efficiency, patient comfort, and reduces alveolar bone resorption. This article reports an overdenture telesco-pic denture as a treatment option in progressive bone loss, low stability and retention, loss of periodontal proprio-ception and low masticatory efficiency. A 35-years-old female came to RSGM Unhas, with complaints of difficulty chewing food due to the loss of several posterior teeth of the upper jaw and lower jaw. The patient felt pain when chewing due to cavities. The patient wanted to retain the remaining teeth and wanted minimal denture-covered mu-cosa. After considering all factors, a telescopic overdenture removable denture RA and RB was recommended. Intraoral examination dental caries 13,11,21,22,23,34,35,45; edentulous 12,14,16,24,25,37,36,44,46 anterior deep bite, normal occlusion. It was concluded that the evaluation of occlusion, aesthetics, phonetics and comfort show-ed that the patient was satisfied, could speak, chew well while using his denture.